Immunoproteasome functions explained by divergence in cleavage specificity and regulation - Michael B Winter; Florencia La Greca; Shirin Arastu-Kapur; Francesco Caiazza; Peter Cimermancic; Tonia J Buchholz; Janet L Anderl; Matthew Ravalin; Markus F Bohn; Andrej Sali; Anthony J O'Donoghue; Charles S Craik (eLife, 2017)
The immunoproteasome (iP) has been proposed to perform specialized roles in MHC class I antigen presentation, cytokine modulation, and T cell differentiation and has emerged as a promising therapeutic target for autoimmune disorders and cancer. However, divergence in function between the iP and the constitutive proteasome (cP) has been unclear. A global peptide library-based screening strategy revealed that the proteasomes have overlapping but distinct substrate specificities. Differing iP specificity alters the quantity of production of certain MHC I epitopes but does not appear to be preferentially suited for antigen presentation. Furthermore, iP specificity was found to have likely arisen through genetic drift from the ancestral cP. Specificity differences were exploited to develop isoform-selective substrates. Cellular profiling using these substrates revealed that divergence in regulation of the iP balances its relative contribution to proteasome capacity in immune cells, resulting in selective recovery from inhibition. These findings have implications for iP-targeted therapeutic development.